Design and simulation of compressive snapshot multispectral imaging system - Ding, Mengjia (Cranfield University, 2018)
Compressive Snapshot Spectral Imaging combines compressive sensing and snapshot spectral imaging (SSI) for restoring the image of the scene in both spatial and spectral contexts by using only a fewer number of sampling measurements of the captured image under the sparsity assumption. SSI is often realised through a coded aperture mask together with a single dispersive element as the main spatial modulator to implement compressive sampling. As one of the representative frameworks in this field, Coded Aperture Snapshot Spectral Imagers (CASSI) has prototyped a low-cost, compact platform to achieve compressive snapshot spectral imaging in the recent decade. Active research in the field includes advanced de-compressive recovery algorithms and also the employment of more sophisticated optical hardware for the design of more robust SSI system. This research addresses more of the latter direction and it focuses on how the CASSI framework can be further developed for various applications such as magnetic resonance imaging for medical diagnosis, enhancement of radar imaging system, facial expression detection and recognition, digital signal processing with sparse structure in terms of image denoising, image super-resolution and image classification. This thesis presents a summary of the research conducted over the past 4 years about the basic property of the CASSI system, which leads to the development of the spectral tuneable SSI design proposed during the course of the PhD study. This new design utilises a Dual-Prism assembly to embed the capability of wavelength-tuning without physically changing its optical elements. This Dual-Prism CASSI (DP-CASSI) adapts to dynamic environments far better than all the CASSI types of imagers published in the open domain which only function for a fixed set of wavelengths. This piece of work has been vii accepted by journal papers for publication. Other contributions of this research has been the enhancement of the Single-Prism (SP-CASSI) architecture and to produce a snapshot system with less aberration and better image quality than that published in the open domain. Moreover, the thesis also provides information about optical design of four different types of CASSI with slightly in-depth analysis about their optical system constructions, optical evaluations of system structure and their dispersive capabilities as the background of this research. Then a more detailed description of the proposed DP-CASSI with respected to its design and performance evaluation particularly its dispersion characteristics and the effects of system resolutions, are given. System verifications were conducted through ray-tracing simulation in three-dimension visualisation environments and the spectral characteristics of the targets are compared with that of the ground truth. The spectral tuning of the proposed DP-CASSI is achieved by adjusting the air gap displacement of dual-prism assembly. Typical spectral shifts of about 5 nm at 450 mm and 10 nm at 650 nm wavelength have been achieved in the present design when the air gap of the dual-prism is changed from 3.44 mm to 5.04 mm. The thesis summaries the optical designs, the performance and the pros and cons of the DP-CASSI system